BLOK, T.A. Inventory of documents - BLOK, T.A. (ARCA, 2018)
Private papers of T.A. Blok, headmaster in Bloemfontein and secretary of the OFS Teachers Society.
COVERAGE 1920; 2 Files; 0.11 metre
Keywords: BLOK, T. A. ; Bloemfontein; Headmaster